CARDIORESPIRATORY DISEASES IN BRAZIL: MORTALITY ANALYSIS AND IMPACTS IN MUNICIPALITIES OF THE COUNTRYSIDE OF GOIÁS (CIPEEX, 2025)
Cardiorespiratory diseases represent a serious public health problem in Brazil, ranking as the leading cause of death in the country. In 2023, around 400,000 Brazilians lost their lives due to 18 such diseases. Although some analyses point to stability in mortality rates from cardiorespiratory diseases, the high incidence and mortality, especially in states such as Goiás, highlight the need for investigations into contributing factors and interventions to mitigate this scenario.Investigating the high mortality from cardiorespiratory diseases in Brazil, with a focus on the high rates of myocardial infarction and other conditions in Goiás, seeks to understand the contributing factors. The data were collected through field research conducted at municipal health departments in Goiás, using data analysis techniques to obtain the best results. Given the gradual increase in mortality rates from cardiorespiratory diseases in Goiás during the period 2023/2024,significant data were identified in smaller towns with relatively low populations. For example, Nova Glória reported 43 deaths, ltapaci, in total, 239 deaths,Ipiranga, 5 deaths, Rubiataba, 33 deaths, and São Patrício, 8 deaths. Thus, research shows that diseases related to the cardiovascular system are the main causes of the aforementioned statistics, affecting about 0.20% of the Brazilian population. It is concluded that such results demonstrate the critical nature of the situation, making investments in prevention, faster diagnoses, and more accessible and humanized care essential.
Keywords: Doenças cardiopulmonares; Mortalidade; Goiás; Prevenção